CBIO-12. GTP METABOLIC SWITCH LEADS TO NUCLEOLAR TRANSFORMATION AND MALIGNANT GROWTH OF GLIOBLASTOMA - Satoshi, Kofuji (Neuro Oncol, 2017)
Nucleolar mass is frequently increased in malignant cells, pointing to a prominent role for aberrant rRNA transcription in highly anabolic cells. ATP and GTP, fundamental energy currencies and building blocks for DNA and RNA, are synthesized by the energy-efficient salvage pathway and energy-demanding de novo pathway. While purine nucleotide biosynthesis is upregulated in malignant cancers, distinctive role(s) of de novo ATP and GTP biosynthesis in cancer cell proliferation remains elusive. Here, we show that the highly lethal brain cancer glioblastoma rewires purine metabolism to activate de novo GTP biosynthesis for rRNA transcription and nucleolar transformation, whereas de novo ATP biosynthesis is commonly utilized in glioblastoma and primary glial cells. Transcriptome screening followed by two cohort analyses identified upregulation of inosine monophosphate dehydrogenase-2 (IMPDH2) in glioblastoma patients. Pharmacological and genetic inhibition of IMPDH2 abolished de novo GTP biosynthesis and growth of glioblastoma cells in vitro and in vivo without affecting de novo ATP biosynthesis. This GTP metabolic switch in glioblastoma cells is critical for enhanced RNA Pol I-dependent nucleolar transcription, but not for RNA Pol II and Pol III transcription. Increased IMPDH2 expression correlates with enlarged nucleoli in human glioma patients, and inhibition of IMPDH2 leads to decreased nucleolar mass. Abnormal nucleolar morphology in many cancer types has long been recognized by pathologists and de novo purine biosynthesis was discovered in 1885. Our data connect these dots of long observed features in cancer by demonstrating a glioblastoma-specific shift in glucose flux to increase de novo GTP biosynthesis, which is required for enhanced ribosome biosynthesis and growth of tumor cells. Our results propose new strategies for the detection and treatment of the incurable glioblastoma, and perhaps other tumors, with minimum impact on normal tissues.